Isomerisation of Liquid‐Crystalline Tristriazolotriazines. Issue 1 (6th December 2017) - Rieth, Thorsten; Röder, Nico; Lehmann, Matthias; Detert, Heiner
Abstract: Star‐shaped discotic liquid crystals with columnar superstructures constitute a highly interesting class of organic materials. Phenyl‐substituted tris[1, 2, 4]triazolo‐[1, 3, 5]triazine, prepared by a Huisgen reaction of phenyltetrazole and cyanuric chloride, represents an excellent core for discotic liquid crystals (DLCs). The thermal stability is not perfect, at temperatures above the clearing point, a successive threefold isomerization leads to a highly planar, C 3 ‐symmetrical isomer, which mainly differs in the orientation of the aryl substituents to the centre of the molecule. A new class of discotic liquid crystals has been obtained: Equipped with peripheral alkoxy chains both isomers can form broad thermotropic mesophases. The optical, thermal, and physical properties were investigated by polarized optical microscopy, differential scanning calorimetry, wide‐angle X‐ray scattering, UV/Vis absorption and fluorescence spectroscopic measurements. The thermotropic properties are decisively affected by the molecular structure of the isomers, isomerisation leads to higher melting points but also the loss or even gain of mesomorphism is observed. Abstract : Seeing stars : A thermal rearrangement of discotic tristriazolotriazines converts Huisgen type all‐tangential, C 3 ‐symmetrical TTTs in three steps via two non‐symmetrical isomers to also C 3 ‐symmetrical but all‐radial isomers. According to the substitution pattern, liquid crystallinity is changed, destroyed, or even gained.